Metal flux from hydrothermal vents increased by organic complexation - Sander, Sylvia G.; Koschinsky, Andrea (Nature geoscience, 2011)
Hydrothermal vents in the sea floor release large volumes of hot, metal-rich fluids into the deep ocean. Mounting evidence suggests that organic compounds bind to and stabilize metals in hydrothermal fluids, thereby increasing metal flux to the open ocean. Hydrothermal vents in the sea floor release large volumes of hot, metal-rich fluids into the deep ocean. Until recently, it was assumed that most of the metal released was incorporated into sulphide or oxide minerals, and that the net flux of most hydrothermally derived metals to the open ocean was negligible. However, mounting evidence suggests that organic compounds bind to and stabilize metals in hydrothermal fluids, increasing trace-metal flux to the global ocean. In situ measurements reveal that hydrothermally derived chromium, copper and iron bind to organic molecules on mixing with sea water. Geochemical model simulations based on data from two hydrothermal vent sites suggest that complexation significantly increases metal flux from hydrothermal systems. According to these simulations, hydrothermal fluids could account for 9% and 14% of the deep-ocean dissolved iron and copper budgets respectively. A similar role for organic complexation can be inferred for the hydrothermal fluxes of other metals, such as manganese and zinc.